Implementasi Balance Scorecard Sebagai Pengukuran Hasil Kinerja Koperasi Karyawan: (Studi Kasus Pada PTPN XII (Persero) Kebun Blawan) - Fredy Eka Ardhi Pratama; Dewi Kurniawati; Wenny Dhamayanthi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
The research location is the Employee Cooperative of PTPN XII (Persero) Region II Kebun Blawan. The research objective is to determine the performance of the Employee Cooperative from the four perspectives of the BSC approach. The sampling method is simple cluster sampling. The number of samples is 67 respondents. Research conclusions (1) Increasing the effectiveness increases the Return On Investment (ROI). (2) Innovations carried out by cooperatives to increased customer satisfaction. (3) In the Internal Business Perspective, operating efficiency so that the operating profit margin increases 3.87% and the operating expense ratio when income increases 16.92%. (4) Learning and growth perspective, increasing employee productivity every year. (5) Performance appraisal during the research period, namely from 2019 to 2021, obtained a performance result of 94.99%; 116.55%; 97.18%.